Design of a Circular Ring Slot Patch Antenna at 2.45 GHz for Hyperthermia Applications - Singh A.; Singh P.; Singh S.P. (My University, 2025)
Hyperthermia plays an important role in the treatment of cancer. A circular ring slot patch antenna for Hyperthermia applications is presented at 2.45 GHz. The proposed antenna shows return loss without significant detuning or impedance mismatch with different positions concerning a phantom muscle model. The simulation study is done by a Finite Element Method (FEM) based on Ansoft’s HFSS software. The antenna penetration depth, return loss, and the specific absorption rate (SAR) pattern are evaluated for various antenna orientations concerning the phantom muscle model. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.